Penegakan Hukum terhadap Tindakan Pembangunan Kontruksi pada Sumber Air Tanpa Izin - Muhammad Luthfi Saputra; Suwari Akhmaddhian (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Water resources (SDA) are a vital basic need for human life, but their management is often misused, which is detrimental to the environment. In Indonesia, the management of SDA is regulated by various regulations, including Law No. 17 of 2019, which regulates the licensing mechanism for the utilization of SDA. This study aims to analyze the regulation of construction permits on water sources and the implementation of the law against unauthorized construction acts through a case study of Supreme Court decision No. 1932 K/PID.SUS/2016. The research method used is normative juridical with an analytical prescriptive approach, which examines related laws and regulations and relevant legal decisions. The results show that water resource licensing regulations require all activities related to SDA to obtain permits from the authorities. The case studied shows that the defendant carried out construction on a water source without a valid permit, violating the provisions of Law No. 7 of 2004 and Law No. 17 of 2019, and causing damage to the surrounding environment. This study concludes that law enforcement against violations of natural resource permits needs to be strengthened to prevent environmental damage and ensure sustainable natural resource management.